2008
DOI: 10.1037/0021-9010.93.5.1139
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the handshake in employment interviews.

Abstract: The authors examined how an applicant's handshake influences hiring recommendations formed during the employment interview. A sample of 98 undergraduate students provided personality measures and participated in mock interviews during which the students received ratings of employment suitability. Five trained raters independently evaluated the quality of the handshake for each participant. Quality of handshake was related to interviewer hiring recommendations. Path analysis supported the handshake as mediating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 53 publications
1
84
0
1
Order By: Relevance
“…The practitioners, for example, reported that they believed a firm handshake to have significantly more impact on career success than an individual's accent. Although a firm handshake has been found to influence recruiters' impressions of candidates (Stewart et al, 2008), there is a wealth of research which demonstrates the extensive impact that accent has on perceptions of personality, likeability, credibility, honesty, IQ, competence, employability and status, and evidence demonstrates that accent feeds into discrimination based on race, sexuality, ethnicity and class (see Carlson and McHenry, 2006, for a review). The breadth of the impact that accent has on perceptions and the comparative weight that the literature places on accent over handshake is at odds with the practitioners' view that accent is far less influential than handshake.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The practitioners, for example, reported that they believed a firm handshake to have significantly more impact on career success than an individual's accent. Although a firm handshake has been found to influence recruiters' impressions of candidates (Stewart et al, 2008), there is a wealth of research which demonstrates the extensive impact that accent has on perceptions of personality, likeability, credibility, honesty, IQ, competence, employability and status, and evidence demonstrates that accent feeds into discrimination based on race, sexuality, ethnicity and class (see Carlson and McHenry, 2006, for a review). The breadth of the impact that accent has on perceptions and the comparative weight that the literature places on accent over handshake is at odds with the practitioners' view that accent is far less influential than handshake.…”
Section: Discussionmentioning
confidence: 99%
“…We drew on key methodological thinking in relation to online surveys in the design, recruitment and analysis of this survey (e.g. Couper, 2008;Evans & Mathur, 2005;Hooley, Marriott & Wellens, 2012 Huffcutt et al, 2013, Stewart et al, 2008. Qualitative comments from the career practitioners who completed the survey indicated that the list did not paint a full picture of the topics discussed within career conversations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of interpersonal skills being interpreted differently is the handshake. A firm handshake creates a positive impression at interview but evidence suggests (Stewart et al, 2008) that the impact is stronger for women than for men, on the grounds that interviewers expect women to have weaker handshakes, so are particularly struck by a strong female grip.…”
Section: Gendermentioning
confidence: 99%
“…Voices, for example, play their part in determining success at interview with employers linking a low pitched voice to a dominant character. The handshake too, within Western cultures, has an impact (Stewart, Dustin, Barrick, & Darnold, 2008) with interviewers inferring sociability, friendliness and dominance from a firm grip.…”
Section: Interpersonal Skillmentioning
confidence: 99%